Detection of an MN1::ETV6 Gene Fusion in a Case of Acute Myeloid Leukemia with Erythroid Differentiation: A Case Report and Review of the Literature - Choate, Lauren A.; Jiang, Liuyan; Stein, Mariam I.; Shen, Wei; Baughn, Linda B.; Peterson, Jess F. (Case Reports in Hematology, 2023)
The MN1::ETV6 gene fusion resulting from t(12;22)(p13;q12) has been rarely reported in myeloid neoplasms. We describe a 69-year-old male with newly diagnosed acute myeloid leukemia (AML) with erythroid differentiation and t(12;22)(p13;q12) demonstrated by conventional chromosome studies. Subsequent fluorescence in situ hybridization studies demonstrated a balanced ETV6 gene rearrangement (at 12p13). To further characterize this translocation, whole-genome sequencing was performed which confirmed t(12;22) with breakpoints involving the MN1 and ETV6 genes. Herein, we describe our case and review the literature to summarize the clinical and laboratory findings in patients with this rare but recurrent MN1::ETV6 gene fusion observed in myeloid neoplasms. Importantly, this case expands the clinical spectrum associated with the MN1::ETV6 gene fusion to include AML with erythroid differentiation. Lastly, this case demonstrates the importance of moving toward more comprehensive molecular testing to fully characterize the driver events in neoplastic genomes.